Docetaxel and paclitaxel: comparison of their pharmacology and mechanisms of resistance - Szczylik, Cezary; Bodnar, Lubomir; Miedzińska-Maciejewska, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2004)
There are two well-known taxanes, that is docetaxel and paclitaxel which are frequently used in clinics. Both drugs are obtained by chemical semisynthesis from coniferous tree Taxus baccata. Location of two different chemical groups at carbon 10 and 13 has a main contribution to anti-cancer activity both taxanes and basic mechanisms of cytotoxicity of paclitaxel and docetaxel which rely on polymerization of tubulin without depolymerization of microtubules. In turn, the latter mechanisms are involved in other proteins such as microtubule-associated proteins various proteins being the regulators of the cell cycle and apoptosis. Paclitaxel has a non- -linear pharmacokinetics with a two compartment model of distribution. Docetaxel has a linear pharmacokinetics with a three compartment model of distribution. Basic scientific experiments and clinical data have shown that mechanisms of resistance are complex. All the latter mechanisms of resistance can be either considered as decreased input of drug within a cell or as worse response to therapy because of altered targeted proteins. There are various mechanisms known that play a key role in pumping the drugs out of the cell through P 170, a protein which is coded by the MDR-1 gene. The targeted proteins are considered as stable microtubules with their main chemical ingredient known as tubulin and other protein associated with microtubules (MAP, protein tau). Preclinical and clinical data taken together, have shown the cross-resistance between paclitaxel and docetaxel.